2020
DOI: 10.1038/s41598-020-65219-2
|View full text |Cite
|
Sign up to set email alerts
|

Sulfonamides-induced oxidative stress in freshwater microalga Chlorella vulgaris: Evaluation of growth, photosynthesis, antioxidants, ultrastructure, and nucleic acids

Abstract: Sulfadiazine (SD), sulfamerazine (SM1), and sulfamethazine (SM2) are widely used and disorderly discharged into surface water, causing contamination of lakes and rivers. However, microalgae are regard as a potential resource to alleviate and degrade antibiotic pollution. the physiological changes of Chlorella vulgaris in the presence of three sulfonamides (SAs) with varying numbers of-cH 3 groups and its SA-removal efficiency were investigated following a 7-day exposure experiment. Our results showed that the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(12 citation statements)
references
References 66 publications
1
10
0
Order By: Relevance
“…The results specified that the protein remained moderately stable. Increasing the protein content of diatoms at low antibiotic concentrations was justified by Chen et al [54]. This increase was related to the increase in enzyme synthesis or other energy-producing fractions.…”
Section: Toxicity Of Antibioticsmentioning
confidence: 96%
See 1 more Smart Citation
“…The results specified that the protein remained moderately stable. Increasing the protein content of diatoms at low antibiotic concentrations was justified by Chen et al [54]. This increase was related to the increase in enzyme synthesis or other energy-producing fractions.…”
Section: Toxicity Of Antibioticsmentioning
confidence: 96%
“…In high antibiotic concentrations, the decrease in chlorophyll and carotenoid contents was justified with the reactive oxygen species (ROS)-mediated damage to the photosystem and chlorophyll biosynthesis in microalgae. Chlorophyll of cells may be used as a protective method to reduce the accumulated ROS in chloroplasts [54].…”
Section: Toxicity Of Antibioticsmentioning
confidence: 99%
“…The toxic effects of sixteen antibiotic classes including aminoglycosides, beta-lactams, tetracyclines, and quinolones presented as median effective concentrations (EC 50 ) are based mainly on biomass endpoints, including growth inhibition and cell density. The most studied antibiotic group based on the number of records regarding EC 50 values is quinolones with 78 records, followed by tetracyclines (55 records), macrolides (58), sulphonamides (44), amphenicols (27), diaminopyrimidine and beta-lactams (26 and 27), lincosamides (15), aminoglycosides (9), quinoxalines and nitroimidazoles (3), pleuromutilins and cephalosporins (2), rifamycins (1), and oxazolidinones (1). The most studied antibiotic is oxytetracycline with 29 records on the median effective toxicity towards green algae (four), cyanobacteria (nine), and diatom (one), respectively (followed by trimethoprim (26 records), erythromycin (21), and enrofloxacin, tylosin and sulfamethoxazole (15)).…”
Section: Summary Of Available Toxicity Data On Individual Antibioticsmentioning
confidence: 99%
“…Many studies have demonstrated the reduced photosynthetic efficiency and pigment content as a result of antibiotic exposure [ 42 , 43 ]. Previous research showed that some antibiotics inhibit chlorophyll synthesis by interfering with gene expression of the chloroplast, thus disrupting the physiological process of photochemical reactions [ 44 ]. The variations in chlorophyll a fluorescence kinetics defined as O, J, I, and P steps of redox states of photosystems PSI and PSII are directly related to the efficiency of electron transfer.…”
Section: Summary Of Available Toxicity Data On Individual Antibiotmentioning
confidence: 99%
“…Furthermore, oxidative stress increases the activity of SOD and glutathione reductase, while decreases the activity of catalase. This made the antioxidant response inadequate to cope with the rising ROS and prevent oxidative damage ( Chen et al, 2020a ). Studies have shown that the co-occurrence of MPs and antibiotics decreases microbial activity and diversity in natural environments such as soil and nitrifying sludge, resulting in combined pollution ( Wang et al, 2020a , b ).…”
Section: Introductionmentioning
confidence: 99%